A Health Impact and Economic Loss Assessment of O3 and PM2.5 Exposure in China From 2015 to 2020. (25th March 2022) - Zhang, Xiangxue; Cheng, Changxiu; Zhao, Hui
Abstract: China is in a critical air quality management stage. Rapid industrial development and urbanization has resulted in non‐ignorable air pollution, which seriously endangers human health. Assessment of the health impacts and economic losses of air pollution is essential for the prevention and control policy formulation. Based on ozone (O3 ) and fine particulate matter concentration (PM2.5 ) monitoring data in 331 Chinese cities from 2015 to 2020, this study evaluated the health effects and the corresponding economic losses of O3 and PM2.5 pollution on three health endpoints. The ratio of population exposed to O3 levels that exceeded the Chinese Ambient Air Quality Standards (CAAQS) increased from 13.35% in 2015 to 14.15% in 2020, which resulted in 133, 415 (2015) ‐ 156, 173 (2020) all‐cause deaths, 88, 941 (2015) ‐ 104, 051 (2020) cardiovascular deaths, and 28, 614 (2015) ‐ 33, 456 (2020) respiratory deaths. The ratio of population exposed to PM2.5 levels that exceeded the CAAQS decreased, but in many regions, especially in North China and the Yangtze River Delta, the PM2.5 concentration remained high. By 2020, nearly half of the population in China was still exposed to PM2.5 levels that exceeded the CAAQS, and the corresponding economic losses reached CNY 3.46 and 3.05 billion, respectively. These results improved the understanding of the spatial‐temporal variation trends of major air pollutants at city scale in China, and emphasize the continued coordination urgently needed for controlling O3 and PM2.5 following the implementation of the 2013 policy to mitigate air pollution to protect human health. Plain Language Summary: Based on ozone (O3 ) and fine particulate matter concentration monitoring data in 331 Chinese cities from 2015 to 2020, this study adopted the health impact assessment model to evaluate the health effects of O3 and PM2.5 pollution on three health endpoints: premature, cardiovascular and respiratory mortality. Key Points: PM2.5 showed a significant decrease but still severe impacts on human health Ozone (O3 ) is posing an increasingly serious threat to human health and economic loss in China Coordinated control of PM2.5 and O3 is essential